Open society unresolved: the contemporary relevance of a contested idea - Royer, Christof ca. 20./21. Jahrhundert; Matei, Liviu (Central European University Press, 2023)
"Is the concept of open society still relevant in the 21st century? Do the current social, moral, and political realities call for a drastic revision of this concept? Here fifteen essays address real-world contemporary challenges to open society from a variety of perspectives. What unites the individual authors and chapters is an interest in open society's continuing usefulness and relevance to address current problems. And what distinguishes them is a rich variety of geographical and cultural backgrounds, and a wide range of academic disciplines and traditions.While focusing on probing the contemporary relevance of the concept, several chapters approach it historically. The book features a comprehensive introduction to the history and current 'uses' of the theory of open society. The authors link the concept to contemporary themes including education, Artificial Intelligence, cognitive science, African cosmology, colonialism, and feminism. The diversity of viewpoints in the analysis reflects a commitment to plurality that is at the heart of this book and of the idea of open society itself"--